The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0103-84782009005000171
|View full text |Cite
|
Sign up to set email alerts
|

Isolamento de Salmonella Braenderup em arara-azul (Anodorhynchus hyacinthinus)

Abstract: Palavras

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…Enterobacteria of the genera Klebsiella, Enterobacter, Morganella, Hafnia and Serratia were less frequently isolated in this study; however, their isolation in wild birds was previously reported in other studies (Gibbs et al, 2007;Santos et al, 2010). Those bacteria are responsible for occasional infections and, in some cases, can function as primary pathogens (Gerlach, 1994, Hidasi et al, 2013, Davies et al, 2016 The absence of Salmonella was also observed in other Brazilian studies, with low detection rates in apparently healthy wild birds, whether maintained in captivity or in the wild (Allgayer et al, 2009;Santos et al, 2010;Lopes et al, 2015, Machado et al, 2016. Because psittacines are very sensitive to avian salmonellosis, particularly at young ages , the absence of Salmonella spp in the present study suggests that the evaluated birds were not exposed to any pathogen of this genus (Godoy, 2007).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Enterobacteria of the genera Klebsiella, Enterobacter, Morganella, Hafnia and Serratia were less frequently isolated in this study; however, their isolation in wild birds was previously reported in other studies (Gibbs et al, 2007;Santos et al, 2010). Those bacteria are responsible for occasional infections and, in some cases, can function as primary pathogens (Gerlach, 1994, Hidasi et al, 2013, Davies et al, 2016 The absence of Salmonella was also observed in other Brazilian studies, with low detection rates in apparently healthy wild birds, whether maintained in captivity or in the wild (Allgayer et al, 2009;Santos et al, 2010;Lopes et al, 2015, Machado et al, 2016. Because psittacines are very sensitive to avian salmonellosis, particularly at young ages , the absence of Salmonella spp in the present study suggests that the evaluated birds were not exposed to any pathogen of this genus (Godoy, 2007).…”
Section: Discussionsupporting
confidence: 60%
“…The enterobacteria detected in this research study is explained by the fact that young birds are colonized by microbes immediately after hatch, and acquire a microbial biomass by contact with environmental microorganisms, as well as by parental feeding, both of which considered the main sources of microbial transmission to developing birds (Mills et al, 1999). Moreover, the young birds may have acquired this harmful microbial load by direct contact with other animals that might have visited the artificial nests, such as mice, bats, and other avian species, or by indirect contact with their secretions (Allgayer et al, 2009;Serafini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The attachment of the organism to fruits and vegetables is a pre-requisite for Salmonella to colonize and be subsequently transmitted to humans and animals. Once it is attached to the fruits and vegetables it is very difficult to remove by washing [6,[47][48][49].…”
Section: Fruits and Vegetables As Vectors Of Transmission Of Salmonellamentioning
confidence: 99%
“…Salmonellosis is caused by the enterobacterium Salmonella, which has high endemicity and morbidity and is very difficult to control (HOFER; FILHO; REIS, 1997). Its main route of transmission is oral and/or fecal, and transmission occurs indirectly through the ingestion of contaminated food or directly through contact with infected wild or domestic animals (ALLGAYER et al, 2009;MURRAY, 2000). It is also of great risk to public health because infected animals can spread this disease to ABSTRACT: A large proportion of emerging infectious diseases (60.3%) globally are zoonotic pathogens, and of these, 71.8% originate from wild animals.…”
Section: Introductionmentioning
confidence: 99%